Development of Derivative Understanding Task Instruments to Explore Student Commognition - Rita Lefrida; Tatag Yuli Eko Siswono; Agung Lukito (Jurnal Pendidikan Matematika, 2023)
Instruments are tool that used to collect research data. The instrument consists of two types, namely the main and supporting instruments. In this paper, we develop the supporting instruments which are used in qualitative research such as commognitive perspective. The instrument development aims to explore and reveal students' cognition in understanding derivative tasks that are valid and reliable. It means the instrument is needed in order to explore cognition and communication in an inseparable manner according to the theory used in this research. The two supporting instruments that developed in this study are the mathematical ability test (MAT) and the derivatives understanding task (TMT). Moreover, the developed MAT instrument is accompanied by source questions, grids and indicators. The MAT consists of 10 questions, and this was tested empirically in the category of valid and high reliability. Furthermore, TMT is developed as a reference for exploring student commognition. The TMT consists of 14 questions. The preparation and development of the instruments in this study are based on relevant theories and supported by empirical data. At the expert review step, validation is carried out in terms of content, construct and language by experts. Each step is tested for readability, then suggestions and comments are provided for improvement. The final results obtained show that the two supporting instruments (MAT and TMT) are feasible to use in exploring student commognition because these bring up keywords, visual mediators, endorsed narratives, and routines, as a commognition characterher.